Ehlers-Danlos Syndrome Type VIII: A Rare Cause of Leg Ulcers in Young Patients. (3rd October 2013) - Ronceray, Sophie; Miquel, Juliette; Lucas, Antoine; Piérard, Gérald E.; Hermanns-Lê, Trinh; De Paepe, Anne; Dupuy, Alain
Abstract : Ehlers-Danlos syndrome type VIII (EDS-VIII) is a very rare autosomal dominant disease characterized by early-onset periodontitis associated with features of Ehlers-Danlos syndrome. We report a 32-year-old man whose chronic leg ulcer led to the diagnosis of EDS-VIII. He had severe periodontitis with complete loss of permanent teeth and skin fragility with thin skin, atrophic scars, and brownish atrophic pretibial plaques. Leg ulcer is not a prominent feature of EDS-VIII. We suggest adding EDS-VIII to the list of rare diseases accounting for chronic leg ulcers, if this case report prompts others to report leg ulcers associated with EDS-VIII.